A shrinking core model for Nannochloropsis salina oil extraction using subcritical water. (February 2019) - Eikani, Mohammad H.; Khandan, Nahid; Feyzi, Elnaz; Ebrahimi, Iman M.
Abstract: In this study, subcritical water extraction (SCWE) was used for dynamic extraction of crude oil of Nannochloropsis salina . The effect of three parameters including water temperature, flow rate and sample loading on the extraction efficiency was investigated and the whole process was simulated by using a two-phase mathematical model. Water temperature, flow rate and sample loading were varied from 150 to 200 °C, from 1 to 4 mL/min and from 1 to 4 g, respectively. The best operating conditions were selected to be 175 °C, 4 mL/min and 1 g and at those conditions, the fatty acids profile was compared with the Folch method. Because of the nature of the biomass and small particle sizes of the cells, a mathematical model based on the shrinking core model (SCM) was developed to evaluate the behavior of the extraction process. Kinetic parameters of the model incl. external film mass transfer coefficient (kf ), solute-solvent binary diffusion coefficient (D12 ), axial dispersion coefficient (Dax ) and effective diffusivity (De ) in solid particle were determined. The later one was selected as the tuning parameter of the model and the others were attained from available correlations. The model predictions were in good agreement with experimental data. Graphical abstract: Highlights: Extraction of Nannochloropsis salina oil using subcritical water was investigated. Optimum operating conditions was obtained. Modeling SCWE was carried out by the shrinking core model applying effective diffusivity in solid phase as tuning parameter. Modeling and simulation of the process was carried out successfully.